Progressive Commodification of Pancasila Values In Schools: Study of The Implications of Implementing P5 by IPS Teachers - Salsabila, Sofia (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2023)
The profile of Pancasila students is the government's effort to create national character through educational aspects. This strategy realizes the achievement of national education goals, namely to create a nation that has Pancasila character. In forming the character profile of Pancasila students, the role of a teacher, especially social studies teachers, is needed. In forming the character profile of Pancasila students, the role of a teacher, especially social studies teachers, is needed. The purpose of this study was to find out how far the role of the social studies teacher plays in shaping the character of students based on the Pancasila student profile in social studies subjects in driving madrasas. This study uses a qualitative method. The research location is MAN 1 Probolinggo. The sample in this study included madrasa heads, social studies teachers, and curriculum assistants. Collection techniques used interviews, observation, and documentation. Furthermore, the process of testing the validity of the researcher's data used two techniques, namely source triangulation techniques and theoretical triangulation techniques. The results and conclusions, namely social studies teachers in forming a Pancasila student profile at MAN 1 Probolinggo includeFirst, teacher as role model,second, teacher as a motivator,third, teacher as a facilitator, as well fourth, the teacher as evaluator. As for the Pancasila values ​​formed by social studies teachers, there are six indicators of themFirst , have faith, betaqwa to God Almighty, and have good morals.Second, gotomg royomg. Third, berbhineka global. Fourth, independent.Fifth, critical reasoning. As well assixth, creative. The role of the teacher in shaping the profile of Pancasila students has a relevance to Vygotsky's contrutivistic learning theory, in this theory the role of the teacher is related to shaping the character of students. There are inhibiting factors experienced by IPS teachers in forming Pancasila student profiles including the lack of support from parents of students and the lack of maximum performance of IPS teachers in forming Pancasila student profiles.